2021
DOI: 10.3390/ejihpe11030057
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Organizational Self-Efficacy and Self-Esteem among Brazilian Teachers during the COVID-19 Pandemic

Abstract: The purpose of this study was to assess the prevalence of, and the association between burnout, organizational self-efficacy and self-esteem, and to assess the predictive influence of burnout and organizational self-efficacy on self-esteem among Brazilian teachers during the COVID-19 pandemic. Brazilian teachers (n = 302) between 24 and 70 years old (Mage = 46.75, SD = 11.02) participated in this study. Measurement instruments included a sociodemographic questionnaire, the Burnout Assessment Tool, the Organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Two extra records were added after a manual search of another source (Google Scholar). After reading the remaining 93 articles in full, we finally included nine in our meta-analysis [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Exclusion reasons are detailed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two extra records were added after a manual search of another source (Google Scholar). After reading the remaining 93 articles in full, we finally included nine in our meta-analysis [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Exclusion reasons are detailed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Strong, research-based support for educators as well as for children are needed now more than ever. The present collaborative learning program was implemented during the global COVID-19 pandemic when worldwide, teachers and educators have been pushed to their limits and among ECEC professionals in the field, exhaustion and stress has been visible (Eadie et al, 2021;Pereira et al, 2021;Pressley, 2021). Supporting ECEC teams in building new, emotionally supportive practices, and increasing professionals' understanding of their own emotions and needs, can boost professionals' work satisfaction and wellbeing (Tsouloupas et al, 2010;Oliveira et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding burn-out syndrome levels in teachers during the pandemic, only a few studies, showing contradicting results, were found. A study by Pereira et al ( 39 ) found teachers to have overall low levels of burn-out syndrome during the pandemic, whereas other studies showed increased levels of burn-out syndrome ( 40 , 41 ) and its dimensions ( 35 , 40 , 42 , 43 ). However, these studies were not able to compare the levels of burn-out syndrome during the pandemic to the levels of burn-out syndrome before.…”
Section: Introductionmentioning
confidence: 97%